Epithelial iris cyst after cataract surgery - Chaudhry, M; Grover, S; Sood, N; Gupta, R (Nepalese Journal of Ophthalmology, 2012)
We report a case of an epithelial inclusion cyst of the iris following cataract surgery that was successfully treated with en bloc excision, after an unsuccessful attempt with Neodymiumdoped Yttrium Aluminium Garnet (Nd YAG) Laser. A 60-year-old man had undergone cataract surgery two years back. One year later, he developed a pigmented epithelial inclusion cyst of the iris which progressively increased in size. His vision reduced to finger counting close to face as the cyst grew over the pupil. We performed Nd YAG laser cystotomy of the cyst wall initially, but the treated lesion recurred. So we performed an en bloc iris excision of the cyst with sector iridectomy. There was no recurrence as determined by slit lamp examination at six months after treatment. Hence, we conclude that en bloc excision can be used to effectively treat epithelial inclusion cyst of the iris. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5876 NEPJOPH 2012; 4(1): 191-193